Impact of selective reporting of antimicrobial susceptibility testing report on clinicians’ prescribing behavior of antibiotics - Wang, Ying; Zhang, Xinping; Zhou, Qian; Xu, Xiaojun (Frontiers in Pharmacology, 2023)
Background: Selective reporting has important value in antibiotic management. The purpose of this study was to explore the impact of AST selective reporting on prescribing behavior, so as to provide evidence for the implementation and improvement of selective reporting policies in microbiology laboratories at home and abroad. Methods: A cross-sectional study was conducted in a teaching tertiary hospital in China in July 2021. We designed selective reports and routine reports for urinary tract infections caused by Escherichia coli and lower respiratory tract infections caused by Pseudomonas aeruginosa. Questionnaires were conducted among participants by case vignettes, and 116 valid questionnaires were collected. The appropriateness rate of antibiotic prescription and the prescription rate of drug-resistant antibiotics, cephalosporins, fluoroquinolones, and carbapenems were calculated and compared between the selective reporting group and the routine reporting group in each case. Results: In most cases, we found that AST selective reporting could increase the appropriateness rate of antibiotic prescription (P<0.05) and reduce the drug-resistant antibiotic prescription rate (P<0.01), cephalosporin drug prescription rate (P<0.05) and fluoroquinolone drug prescription rate (P<0.01). Although the difference in carbapenems prescription rate was not significant, selective reporting could reduce the number of its prescriptions to some extent. Conclusions: AST selective reporting can help promote the appropriate use of antibiotics and reduce the use of broad-spectrum antibiotics. It is suggested to develop scientific and effective selective reporting practices and strengthen the two-way communication between clinicians and microbiology laboratories, thereby enabling microbiology laboratories to play a more important role in clinical antimicrobial management.